2013
DOI: 10.1371/journal.pone.0070351
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosoglutathione Reductase Inhibition Regulates Allergen-Induced Lung Inflammation and Airway Hyperreactivity

Abstract: Allergic asthma is characterized by Th2 type inflammation, leading to airway hyperresponsivenes, mucus hypersecretion and tissue remodeling. S-Nitrosoglutathione reductase (GSNOR) is an alcohol dehydrogenase involved in the regulation of intracellular levels of S-nitrosothiols. GSNOR activity has been shown to be elevated in human asthmatic lungs, resulting in diminished S-nitrosothiols and thus contributing to increased airway hyperreactivity. Using a mouse model of allergic airway inflammation, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…in 50 ml PBS at doses of 0.3, 1.0, and 3.0 mg/kg daily. These doses were chosen based on the results of the previous studies in a mouse ovalbumin model (Ferrini et al, 2013) as well as our unpublished observations in a house dust mite model of asthma. In those studies, these doses were found to be effective yet safe.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…in 50 ml PBS at doses of 0.3, 1.0, and 3.0 mg/kg daily. These doses were chosen based on the results of the previous studies in a mouse ovalbumin model (Ferrini et al, 2013) as well as our unpublished observations in a house dust mite model of asthma. In those studies, these doses were found to be effective yet safe.…”
Section: Methodsmentioning
confidence: 99%
“…GSNO is present in high levels in lung lining fluid and has been shown to exert bronchodilatory activity with a 100-fold higher potency than theophylline (Gaston et al, 1993(Gaston et al, , 1994. By inhibiting GSNOR, SPL-334 inhibits the catabolism of GSNO, which increases the cellular pool of GSNO and the level of nitroso groups on critical proteins, leading to smooth muscle relaxation, decreased inflammation via inhibition of the nuclear factor-kB (NF-kB) pathway, activation of antioxidant pathways via activation of Nrf-2, and increased mucin clearance (Nozik-Grayck et al, 2002Que et al, 2005;Sanghani et al, 2009;Wu et al, 2010;Kelleher et al, 2011;Foster et al, 2012;Ferrini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, decreased glutathione levels have been suggested to induce changes in T H 1 to T H 2 cell differentiation. Under these circumstances, the oxidant and antioxidant balance is lost and AHR is induce by the synthesis of S-nitrosoglutathione and a corresponding shift in NO metabolism (58,59).…”
Section: Inflammatory Cellsmentioning
confidence: 99%
“…The role of LTC 4 in allergic asthma has been extensively evaluated (85). LTC 4 is produced in mast cells by assembly of a biosynthetic complex at the nuclear envelope, consisting of cytosolic phospholipase A2 (cPLA2), (64) Oxi-CaMKII inhibitor KN-93 KN-93 significantly decreased goblet cell hyperplasia, bronchial epithelial thickness, airway eosinophilia, the eosinophil chemoattractant molecule, Ccl-11, and NF-κB activity in allergic asthma (61) Leukotriene C4 (LTC 4 ) inhibitor A LTC 4 inhibitor reduced NOX4 levels and attenuated cell death (32) Galangin Galangin demonstrated decreased airway remodeling, angiogenic activity, and ASMC proliferation through the TGF-β1-ROS-MAPK pathway (65)(66)(67) Astragalin Astragalin suppressed LPS-induced ROS production and eotaxin-1 expression in epithelial cells through the TLR4-PKCγ1-PKCβ2-NADPH signaling pathway (68,69) Glutathione GSH balances Th1/Th2 responses, alters nitric oxide metabolism and inhibits ROS (55,59,70) SOD SODs protects against the harmful effects of ROS and airway inflammation (71)(72)(73) Glutathione peroxidases Glutathione peroxidases prevent airway inflammation and alveolar destruction (74)(75)(76) Vitamins C and E Vitamins C and E reduce AHR, inflammation, and oxidative stress (77)(78)(79) TLR7, toll-like receptor 7; Oxi-CaMKII, oxidative-CaMKII; SOD, superoxide dismutase; AHR, airway hyper-reactivity; Nrf2, nuclear factor E2-related factor 2; Cu/Zn SOD, copper/zinc superoxide dismutase; ROS, reactive oxygen species; NOX4, NADPH oxidase 4; LPS, lipopolysaccharide; Th2, type 2 helper T.…”
Section: Ltc 4 Inhibitorsmentioning
confidence: 99%